Biografi Syofyani Yusaf Maestro Seni Tari Minangkabau Di Padang - Devina Utami; Herlinda Mansyur; Afifah Asriati (SENDRATASIK UNP, 2019)
This research aims to disclose and describe the biography Syofyani Yusaf Maestro Minangkabau dance art in the field. This type of research is qualitative research using descriptive method. The instrument of this research the researcher himself, and assisted with the supporting instruments such as stationery, photo cameras and audio conversation tool. The type of data in this study is the primary data and secondary data. Engineering data collection done by the study of librarianship, observation/observation, interview and documentation. And the data were analyzed with data reduction steps, the data model (data display) and withdrawal/verification conclusion. The results showed that Syofyani Yusaf was choreographed dance in the Minangkabau region of national and international scale through the karya–karyanya. The success of Yusaf Syofyani seen from the number of achievements – achievements by Yusaf Syofyani including the title Minangkabau Dance Maestro of the President of Republic of Indonesia. From the hands of Syofyani was born the students who come from within the country and abroad. Sanggar Syofyani has dozens of times in the legislation to foreign countries to do dance attractions. The dedication and devotion of Syofyani has been demonstrated with dozens of awards ranging from College, Ministry of tourism, the President of the Republic of Indonesia to the organizers of International Events. Hopes of a Syofyani Yusaf was so that people know how to dance khasan region of West Sumatra (Minangkabau), not just see but when hearing the public knowing that it was the Minangkabau dance performances.Biography; Syofyani Yusaf; Minangkabau; Dance Art Maestro